The New Life of Tavern: Dissolution of a “Great Third Place” - Nevena Milanović (Etnoantropološki Problemi, 2021)
In this paper, through a critical review of the theoretical postulates on the so-called "Shiny third place", I will try to point to the correlation and interdependence of spatial behavior, music, identity and alcohol consumption. I regard these terms as social categories that have emerged, formed in the constant process of transformation, and as such, the subject of anthropological analysis. Starting from the hypothesis that spatial behaviors are a form of identity expression within the framework of social imaginarium, and that identities are multilayered, fragmentary and subject to manipulation, one might ask how today to define a "tavern culture" (culture of a kafana) that once seemed so clear and homogeneous. Through the method of participant observation and the method of in-depth interviews in my work, I will try to answer the following research questions: how to define contemporary tavern culture? Is music the basis for the formation of a tavern culture, and alcohol consumption is a necessary follower and what are its social implications? Through the syntagma Identity Forum, a new theoretical framework will be offered for the consideration of (post)modern taverns and the dissolution of its (established) identity.